Brain metastases in the elderly – Impact of residual tumor volume on overall survival - Baumgart, Lea; Aftahy, Amir Kaywan; Anetsberger, Aida; Thunstedt, Dennis; Wiestler, Benedikt; Bernhardt, Denise; Combs, Stephanie E.; Meyer, Bernhard; Meyer, Hanno S.; Gempt, Jens (Frontiers in Oncology, 2023)
Background: Due to demographic changes and an increased incidence of cancer with age, the number of patients with brain metastases (BM) is constantly increasing, especially among the elderly. Nevertheless, geriatric patients are often overlooked in clinical trials and impact of resection of BM is a frequently debated topic, that remains unclear and needs to be addressed. This study aimed to analyze the impact of resection and residual tumor burden (RTB) of elderly patients with BM to determine significant markers on postoperative clinical outcome and overall survival (OS). Methods: Patients ≥ 75 years and surgery for BM between 04/2007 – 01/2020 were retrospectively included. RTB was segmented using early postoperative MRI(72h). Impact of preoperative KPSS, age, sex and RTB on OS was analyzed. Survival analyses were performed using Kaplan-Meier estimates for univariate analysis and Cox regression proportional hazards model for multivariate analysis. Results: 101 patients were included, median age at surgery was 78 years (IQR 76-81). 62 patients (61%) had a single BM, 16 patients (16%) had two BM, 13 patients (13%) had three BM and 10 patients (10%) had three or more BM. Median preoperative tumor burden was 10.3 cm3(5-25) and postoperative tumor burden 0 cm3(0-1.1). Complete cytoreduction (RTB=0) was achieved in 52 patients (52%). Complete resection of the targeted metastases was achieved in 78 patients (78%).Median OS was 7 months(2-11). In multivariate analysis preoperative KPSS (HR 0.986, 95% CI 0.973-0.998, p=0.026) and postoperative tumor burden (HR 1.025, 95%CI 1.002-1.047, p=0.029) were significant parameters for OS. Hereby, RTB=0 was significantly associated with prolonged median OS compared to RTB>0 (12 months vs. 5 months, p=0.007). Furthermore, prolongation of survival was significantly associated with surgery in patients with a favorable KPSS, with an adjusted HR of 0.986 (p=0.026). However, there were no significances regarding age. Conclusions: RTB is a strong predictor for OS, regardless of age or cancer type. Extent of resection should be confirmed by postoperative MRI as complete resection is not warranted by intraoperative estimates. It is crucial to aim for maximal cytoreduction to achieve the best long-term outcome for these patients, despite the fact they are advanced in age.